Aspectos reprodutivos do rotífero Asplanchna do Brasil - Bertollo, Luiz A. C. (Revista de Biología Tropical, 1978)
Biological aspects of the brazilian retifer Asplanchna sp., reared in the laboratory, were studied and the mean curve of development and its connections with the generation time of amictic females were established. The mean generation time was around 22 hr; thus, the fust offspring of an amictic female were born, on the average, almost at the end of its active growth period. Studies on the longevity of amictic females and on the fecundity in amictic and mictic females were also carried out. The amictic females showed a mean longevity of 90.30 hr and a mean fecundity of 17 female offspring. On the other hand, an unfertilized female produced an average of 13 male offspring or, if fertilized, 4 resting-eggs.